Non-knowledge in Medical Practices: Approaching the Uses of Social Media in Healthcare from an Epistemological Perspective - Anna Sendra; Sinikka Torkkola; Jaana Parviainen (Journal of Digital Social Research)
Social media has transformed how individuals handle their illnesses. While many patients increasingly use these online platforms to understand embodied information surrounding their conditions, healthcare professionals often frame these practices as negative and do not consider the expertise that patients generate through social media. Through a combination of insights from social epistemology and ignorance studies, this paper problematizes the distinctive understandings of social media between patients and healthcare professionals from a different perspective. A total of four ideas are introduced: (1) healthcare professionals see embodied knowledge that arises from patients’ social media practices as uncomfortable knowledge; (2) healthcare professionals engage in several behaviours to preserve their authority and power in front of embodied knowledge created through these online platforms; (3) failing to consider embodied knowledge can have consequences not only in terms of trust between patients and healthcare professionals but also in connection with epistemological populism and the transition towards patient-centred care; and (4) media and digital health literacy could help healthcare professionals enhance the uses of social media in healthcare. Adopting this framework allows not only to offer valuable insights into how healthcare professionals manage patients’ social media practices, but also opens new avenues to improve healthcare digitisation.